2022
DOI: 10.1038/s41598-022-09287-6
|View full text |Cite
|
Sign up to set email alerts
|

More tropical cyclones are striking coasts with major intensities at landfall

Abstract: In this study, we show that the number of annual global tropical cyclone (TC) landfalls with major landfall intensity (LI ≥ 50 m s−1) has nearly doubled from 1982 to 2020. The lifetime maximum intensity (LMI) of global major landfalling TCs has been increasing by 0.8 m s−1 per decade (p < 0.05), but this significance of intensity change disappears at landfall (0.3 m s−1 per decade, p = 0.69). The lack of a significant LI trend is caused by the much larger variance of LI than that of LMI in all basins and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In addition, the spatial heterogeneity in the population growth and economic development cause differences in local exposure to TCP hazards. Potential damage may increase exponentially due to changes in the magnitude and frequency of extreme TC events 53,54 . Compound events such as storm surge and pluvial floods can intensify those damages 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spatial heterogeneity in the population growth and economic development cause differences in local exposure to TCP hazards. Potential damage may increase exponentially due to changes in the magnitude and frequency of extreme TC events 53,54 . Compound events such as storm surge and pluvial floods can intensify those damages 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the maximum intensity of TCs has migrated polewards [32][33][34][35][36][37][38][39][40]. However, it is not clear whether LTCER has undergone similar changes.…”
Section: Characteristics Of Ltcer Amount's Variationmentioning
confidence: 95%
“…The magnitude of increasing trends in the inland areas is relatively larger than that in the coastal areas (figure 4). Recent studies showed that TCs had a poleward and inland migration, meanwhile TCs exhibited a westward shift to land in China [34,40], which likely result in the increase of LTCER in the northern and inland regions, as shown in figure 4. Although LTCER in most inland places increased obviously, LTCER in a few inland areas decreased instead.…”
Section: Characteristics Of Ltcer Amount's Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical cyclones (TCs) are among the most destructive natural disasters that frequently strike densely populated coastal regions (Weinkle et al., 2018). Their intensity, represented by near‐surface maximum wind, is detailed in the literature, including its evolution, prediction, impact and long‐term trends (e.g., Knutson et al., 2019; Walsh et al., 2016; Wang & Toumi, 2022a). Apart from their intensity, the horizontal extent of their outer circulation, commonly termed TC outer size, is another crucial factor that determines their overall destructiveness (e.g., Emanuel, 2005; Irish et al., 2008; Powell & Reinhold, 2007; Wang & Toumi, 2016; Zhai & Jiang, 2014).…”
Section: Introductionmentioning
confidence: 99%